S135 The added value of nasal potential difference measurement when first-line cystic fibrosis (CF) Investigations are non-diagnostic. (December 2018) - Simmonds, NJ; Pabary, R; Kohlhäufl, J; Waller, MD; Alton, EA; Davies, JD
Abstract : Introduction: The diagnosis of CF can be challenging when the sweat chloride (Cl−) value is non-diagnostic (<60 mmol/L) and/or genotyping does not confirm 2 disease-causing mutations. Our Difficult CF Diagnosis (DCFD) Service offers a comprehensive evaluation of such patients, providing a systematic assessment of CFTR function (sweat Cl− and nasal potential difference (nPD) measurement), genetics and phenotype. Methods: Retrospective study of medical records of all patients referred to our DCFD service (2009–2017). Final diagnoses were reached by consensus opinion contemporaneously on review of all available data. Results: 172 patients were reviewed: 129 (75.0%) ≥16 years; 78 (45.3%) male; median (range) age 28.9 (2.9–76.5) years. 136 (79.1%) had a history of chronic lower respiratory tract symptoms (of which 58.2% had bronchiectasis)), 33% chronic sinusitis and 6% pancreatitis. Of male patients≥16 years (n=63), 16 (25.4%) had confirmed congenital bilateral absence of the vas deferens. The median (range) sweat Cl− of the whole group (n=160) was 42.3 (2.0–109) mmol/L; 12 patients produced insufficient sweat. For first-line genotyping (up to 50 mutations) 78 (45.3%) patients had mutations/variants identified (n=24, compound heterozygote – nil diagnostic); extended CFTR analysis increased the diagnostic yield by 3 patients. Using nPD the diagnosis was clarified for 145 (84.3%) patients, by excluding CF (n=101; 58.7%) or confirming CF/CFTR-related disorder (RD) (n=44; 25.6%). The others remained diagnostic uncertainties (n=10), were technical failures (n=7) or were associated with a possible sodium channel defect (n=10). Sodium channel mutation analysis is currently underway. Adults were more likely to have CF/CFTR-RD confirmed than children (30% v 9%). 18 (10.5%) patients had their long-standing CF diagnosis reversed. Conclusions: Our DCFD service – with the inclusion of nPD – improves the diagnostic yield in 84.3% of cases with equivocal first-line CF investigations. With our recently introduced extended ( CFTR and non- CFTR ) genomic service, we expect this will increase further. Our service provides important diagnostic clarity to patients, caregivers and healthcare providers.